The critical requirements for the principalship from an analysis of critical incidents as reported by public elementary school teachers in Manila - Malicdem, Godofredo S. 1907- (University of the Philippines], 1957)
This study determines the critical requirements for principalship. It investigated the effective and ineffective acts related to the principalship and its implications on the principalship preparation progam and in-service training.